Unraveling the degradation mechanism of multiple pyrethroid insecticides by Pseudomonas aeruginosa and its environmental bioremediation potential - Hui Liu; Wen-Juan Chen; Zeling Xu; Shao-Fang Chen; Haoran Song; Yaohua Huang; Kalpana Bhatt; Sandhya Mishra; Mohamed A. Ghorab; Lian-Hui Zhang; Shaohua Chen (Environment International)
Extensive use of pyrethroid insecticides poses significant risks to both ecological ecosystems and human beings. Herein, Pseudomonas aeruginosa PAO1 exhibited exceptional degradation capabilities towards a range of pyrethroid family insecticides including etofenprox, bifenthrin, tetramethrin, D-cypermethrin, allethrin, and permethrin, with a degradation efficiency reaching over 84 % within 36 h (50 mg·L-1). Strain PAO1 demonstrated effective soil bioremediation by removing etofenprox across different concentrations (25–100 mg·kg−1), with a degradation efficiency over 77 % within 15 days. Additionally, 16S rDNA high-throughput sequencing analysis revealed that introduction of strain PAO1 and etofenprox had a notable impact on the soil microbial community. Strain PAO1 displayed a synergistic effect with local degrading bacteria or flora to degrade etofenprox. UPLC-MS/MS analysis identified 2-(4-ethoxyphenyl) propan-2-ol and 3-phenoxybenzoic acid as the major metabolites of etofenprox biodegradation. A new esterase gene (estA) containing conserved motif (GDSL) and catalytic triad (Ser38, Asp310 and His313) was cloned from strain PAO1. Enzyme activity and gene knockout experiments confirmed the pivotal role of estA in pyrethroid biodegradation. The findings from this study shed a new light on elucidating the degradation mechanism of P. aeruginosa PAO1 and present a useful agent for development of effective pyrethroid bioremediation strategies.